The automated lighting programmer's handbook - Schiller, Brad (Routledge, 2017)
This guide helps lighting designers with the creative and operational challenges they face in their rapidly evolving industry. Providing respected and clear coverage of the process of programming automated lighting fixtures, the author brings the designer from basic principles to preproduction preparations. Concepts, procedures, and guidelines to ensure a successful production are covered as well as troubleshooting, much needed information on work relationships, and technology including LED lighting, console networking, digital lighting, and more. Chapters are peppered with advice and war stories from some of the most prominent lighting designers of today.